Urban and rural safety net health care system clinics: no disparity in HPV4 vaccine completion rates. - Kelly Jo Sandri; Inge Verdenius; Mitchell J Bartley; Britney M Else; Christopher A Paynter; Beth E Rosemergey; George D Harris; Gerard J Malnar; Sean M Harper; R Stephen Griffith; Aaron J Bonham; Diane M Harper (PLoS ONE, 2014)
OBJECTIVE:Safety net health care centers in the US serve vulnerable and underinsured females. The primary aim of this work was to determine if HPV4 dosing compliance differs between females who receive doses at rural vs. urban core safety net health care locations. METHODS:Females exclusively receiving health care in the Truman Medical Center (TMC) safety net system at the urban core and rural locations were identified by their HPV4 vaccine records. Dates and number of HPV4 doses as well as age, gravidity, parity and race/ethnicity were recorded from the electronic medical record (EMR). Appropriate HPV4 dosing intervals were referenced from the literature. RESULTS:1259 females, 10-26 years of age, received HPV4 vaccination at either the rural (23%) or urban core location (77%). At the rural location, 23% received three doses on time, equal to the 24% at the urban core. Females seen in the urban core were more likely to receive on-time doublet dosing than on-time triplet dosing (82% vs. 67%, p<0.001). Mistimed doses occurred equally often among females receiving only two doses, as well as those receiving three doses. CONCLUSIONS:Compliance with on-time HPV4 triplet dose completion was low at rural and urban core safety net health clinics, but did not differ by location.